The scrambled states of America - Keller, Laurie (New York : Henry Holt, 1998)
The states become bored with their positions on the map and decide to change places for a while. Includes facts about the states.
CD narrated by Jon Carroll.
Keywords: U.S. states -- Juvenile fiction; U.S. states -- Fiction; U.S. states; United States -- Juvenile fiction; U.S. states; United States; Fiction; Juvenile works